DA adapts Guinayangan CSV model in implementing Php100M AMIA phase 2 projects in 10 regions, mainstreams CSVs in DA's 2019-2022 CSA/CRA program. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
lessons from Establishing Guinayangan CSV, provided PH Department of AGriculture(DA) a model for developing AMIA-Villages (adaptation of CSV). Approaches for participatory action researches, community support systems, and knowledge sharing in a CSV context recognized by the Systems-Wide Climate Change Office(DA-SWCCO) as most relevant in further development and implementation of CRA at local level. These innovations, tested by IIRR, will be the subject of future capacity building initiatives of DA targeting regional field offices, local governments and extension agents.